The impact of COVID-19 and associated measures on health, police, and non-government organisation service utilisation related to violence against women and children - Nadia Butler; Zara Quigg; Isabelle Pearson; Zhamin Yelgezekova; Aasa Nihlén; Mark A. Bellis; Yongjie Yon; Jonathon Passmore; Isabel Yordi Aguirre; Heidi Stöckl (BMC, 2022)
Abstract Background Globally, concerns have been raised that the priority implementation of public health measures in response to COVID-19 may have unintended negative impacts on a variety of other health and wellbeing factors, including violence. This study examined the impact of COVID-19 response measures on changes in violence against women and children (VAWC) service utilisation across European countries. Methods A rapid assessment design was used to compile data including a survey distributed across WHO Europe Healthy Cities Networks and Violence Injury Prevention Focal Points in WHO European Region member states, and a scoping review of media reports, journal articles, and reports. Searches were conducted in English and Russian and covered the period between 1 January 2020 and 17 September 2020. Data extracted included: country; violence type; service sector; and change in service utilisation during COVID-19. All data pertained to the period during which COVID-19 related public health measures were implemented compared to a period before restrictions were in place. Results Overall, findings suggested that there was a median reported increase in VAWC service utilisation of approximately 20% during the COVID-19 pandemic. Crucially, however, change in service utilisation differed across sectors. After categorising each estimate as reflecting an increase or decrease in VAWC service utilisation, there was a significant association between sector and change in service utilisation; the majority of NGO estimates (95.1%) showed an increase in utilisation, compared to 58.2% of law enforcement estimates and 42.9% of health and social care estimates. Conclusions The variation across sectors in changes in VAWC service utilisation has important implications for policymakers in the event of ongoing and future restrictions related to COVID-19, and more generally during other times of prolonged presence in the home. The increased global attention on VAWC during the pandemic should be used to drive forward the agenda on prevention, increase access to services, and implement better data collection mechanisms to ensure the momentum and increased focus on VAWC during the pandemic is not wasted.